2016
DOI: 10.1136/bmjopen-2016-011054
|View full text |Cite
|
Sign up to set email alerts
|

Vascular biomarkers to predict response to exercise in Alzheimer's disease: the study protocol

Abstract: IntroductionExercise interventions are a promising treatment for improving cognition in persons with Alzheimer's disease. This is similar to Alzheimer's disease pharmacotherapies in which only 18–48% of treated patients demonstrate improvement in cognition. Aerobic exercise interventions positively affect brain structure and function through biologically sound pathways. However, an under-studied mechanism of aerobic exercise's effects is n-3 fatty acids in plasma. The objective of this pilot study is to inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Several RCT protocols were published recently aiming to investigate the PA effects on cognition and incorporating different dementia‐related biomarkers of participants with MCI, AD, or dementia 66–71 . Completion of these studies should significantly expand the knowledge base about PA and biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Several RCT protocols were published recently aiming to investigate the PA effects on cognition and incorporating different dementia‐related biomarkers of participants with MCI, AD, or dementia 66–71 . Completion of these studies should significantly expand the knowledge base about PA and biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, objective measurements (e.g. MRI, vascular biomarkers) should be added to assess cognitive function in intervention studies, which could avoid the interference (Li et al, ; Yu et al, ). However, only van der Kleij et al () used brain MRI in the involved studies, and the results showed that moderate‐to‐high intensity exercise was not sufficient to produce a consistent increase in whole or regional cerebral blood flow in patients with AD, especially when the intervention did not last enough time.…”
Section: Discussionmentioning
confidence: 99%
“…After collections, blood specimens were stored immediately on wet ice. A laboratory technician processed and aliquoted these specimens according to an established protocol [ 18 ]. Briefly, plasma EDTA tubes were mixed and centrifuged in 4°C using a temperature-controlled centrifuge with a Swing out Rotor at 1,439 g for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The tubes were removed from the centrifuge immediately after completion. Plasma samples were aliquoted and stored in a –80°C freezer [ 18 ]. Plasma NfL was measured using the Simoa ® NF-light Advantage kit on a HD-1 analyzer (Quanterix, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%